PENCIPTAAN SEKTOR WISATA BAHARI MELALUI MARKETING PUBLIC RELATION (MPR) - La Ode Sugianto; Yusuf Adam Hilman (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2020)
This research study about the concept of MPR In creating tourism sector using descriptive analysis qualitative The results of the study descriptive of the implementation of Marketing public relations (MPR) will be very effectively and efficiently when applied to the creation of marine tourism sector that is Batuatas Island, Can be measured from topicality, credibility, and Involvement The application of the concept of Marketing Public Relations Can provide sustainable relations to all stakeholders both the central government and the regions, and investors. The goal that tourism potential nautical that is on the island Batuatas could be a tourist destination that known at the national level down to international